GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 193829 species occurrences available in GBIF matching the query: Country: Haiti. The dataset includes 193829 records from 447 constituent datasets: 2 records from Collection Crustacea - ZIM Hamburg. 3 records from FBIP:ELM: Malacology Collections. 14 records from Naturalis Biodiversity Center (NL) - Cnidaria. 4 records from Coleção Entomológica do Museu Nacional / UFRJ. 2691 records from University of Florida Herbarium (FLAS). 1 records from Invertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 11 records from Canadian Museum of Nature Herbarium. 3 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 59 records from Meise Botanic Garden Herbarium (BR). 1 records from A systematic appraisal of the types of ten species of Otostigmus (Parotostigmus) (Scolopendromorpha, Scolopendridae, Otostigminae). 10 records from Duke University Herbarium. 15 records from NOAA Deep Sea Corals Research and Technology Program. 2 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 28 records from R. L. McGregor Herbarium Vascular Plants Collection. 2 records from International Fossil Shell Museum (NL) - Mollusca Collection. 6 records from University of Michigan Museum of Zoology, Division of Insects. 12 records from Arizona State University Lichen Collection. 2 records from Marie-Victorin Herbarium (MT) - Bryophytes. 1 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 36 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 6 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 2 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 7 records from University of Vienna, Institute for Botany - Herbarium WU. 60 records from Collection Ichthyologie - SNSD. 1 records from NYSM Birds. 1 records from National Botanic Garden Belgium - Myxomycetes. 2 records from The Vascular Plant Collection at the Herbarium MSB, Universität München. 31 records from Canadian Museum of Nature Palynology Collection. 5 records from SMNK Mantid Collection. 32 records from Sammlung Eggers Westindien Herbarium Hamburgense HBG. 2 records from Itami City Museum of Insects. 30 records from Mississippi Entomological Museum. 18 records from Botany (UPS). 1 records from Lyman Entomological Museum (LEMQ). 274 records from Herbarium Berolinense. 152 records from CAS Herpetology (HERP). 1 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 1 records from CAS Entomology (ENT). 3 records from Lichen herbarium, UiB. 7 records from Orchid Herbarium Collection. 15 records from Nannofossil assemblage in surface sediments. 10 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 345 records from NMNH Paleobiology Specimen Records. 1 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 38031 records from EOD - eBird Observation Dataset. 17443 records from Museum of Comparative Zoology, Harvard University. 1 records from Herpetology Collection NRM. 6 records from SINGER Coordinator. 1 records from A contribution to the knowledge of the centipedes of Saint Barthélemy Island (French Antilles), with re-descriptions of Newportia heteropoda Chamberlin, 1918 and Cormocephalus impressus Porat, 1876 (Chilopoda: Scolopendromorpha). 18571 records from University of Florida Vertebrate Paleontology. 2238 records from University of Michigan Herbarium. 3 records from UCBG TAPIR Provider. 16 records from Arizona State University Hasbrouck Insect Collection. 33 records from Naturalis Biodiversity Center (NL) - Aves. 80 records from International Barcode of Life project (iBOL). 54 records from Catálogo electrónico de especímenes depositados en el Herbario de la Universidad de Texas en Austin, Fase IV. 137 records from Collection Herpetologie - SNSD. 13 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 3 records from Generic key and catalogue of Mymaridae (Hymenoptera) of Mexico. 1 records from Estonian University of Life Sciences. 38 records from University of Michigan Museum of Zoology, Division of Birds. 1 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 77 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 36 records from Duke University Herbarium. 60 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 764 records from Fishbase. 5 records from MEXU/Colección de Briofitas. 1 records from Description of two new species of Nelphe Herrich-Schäffer, with comments on the genus (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina). 2 records from Herbarium Hamburgense. 5 records from The Vascular Plants Collection of the University of Goettingen. 2 records from Instituto de Botánica Darwinion. 11 records from Collection Mollusca SMF. 1 records from The sharpshooter geNUs Apogonalia EvaNs (Hemiptera: Cicadellidae: CicadelliNi): descriptioN of females aNd key to species. 2 records from CHAS Ornithology (Arctos). 4 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 98 records from AMNH Mammal Collections. 1 records from Ouellet-Robert entomological collection (QMOR). 21 records from Moscow University Herbarium (MW). 281 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 1 records from ORN. 61 records from Geographically tagged INSDC sequences. 80 records from University of South Florida Herbarium (USF). 93 records from Bernice P. Bishop Museum. 131 records from LACM Vertebrate Collection. 6 records from University of Michigan Museum of Zoology, Division of Mammals. 3 records from Mollusca Collection - Museu Nacional/UFRJ. 10 records from BYU Herpetology Collection. 2 records from South Australian Museum Australia provider for OZCAM. 1 records from Herbarium of Umeå University (UME). 5 records from Cleveland Museum of Natural History.. 3 records from Universidad Autónoma de Madrid, Biología, Acalypha. 6 records from University of North Carolina Chapel Hill Herbarium. 1 records from NCSM Ichthyology Collection. 1 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 5 records from Marine invertabrate(Mollusca) specimen database of Osaka Museum of Natural History. 7 records from arim. 14 records from Clitellata - SMF. 9 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 1 records from CONN. 1 records from DIPOL. 1 records from The Hasle Collection (Diatoms). 23 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 13 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 1 records from UWIZM Scarabaeidae Beetles. 1 records from UCM Fish Collection (Arctos). 2 records from Molecular and morphological systematics of Elysia Risso, 1818 (Heterobranchia: Sacoglossa) from the Caribbean region. 773 records from Paleobiology Database. 3 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 524 records from UF Florida Museum of Natural History Mammals. 2 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from Collection Crustacea SMF. 3 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv). 206 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 6 records from Collection Crustacea ZMG. 6 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 28 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 96 records from naturgucker. 1 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 1 records from Ghent University - Zoology Museum - Invertebrate collection. 278 records from iNaturalist Research-grade Observations. 1 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 51 records from WFVZ Bird Collections. 22 records from Collection Aves (bird skins) SMF. 2 records from Canadian Museum of Nature Crustacea Collection. 3 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Appalachian State University, I. W. Carpenter, Jr. Herbarium. 1 records from Botany Division, Yale Peabody Museum. 4 records from CSIC-Real Jardín Botánico-Colección de Musgos (MA-Musci). 143 records from MVZ Herp Collection (Arctos). 1 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from SPF - Herbário da Universidade de São Paulo. 1191 records from Harvard University Herbaria: All Records. 3 records from Molluscus specimens of Toyohashi Museum of Natural History. 171 records from AMNH Bird Collection. 6 records from A new species of shrimp of the genus Periclimenaeus Borradaile, 1915 (Decapoda: Caridea: Palaemonidae) from the southeastern Gulf of Mexico, including a key to the western Atlantic species of the genus. 1 records from MVZ Bird Collection (Arctos). 157 records from AntWeb. 6 records from Northern Territory Museum and Art Gallery provider for OZCAM. 19 records from Distribution of planktonic foraminifera in surface sediment samples A180-072 to V23-83. 5 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 15 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 5 records from Rutgers University, Chrysler Herbarium - Bryophyte Collection. 1 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 305 records from Field Museum of Natural History (Botany) Seed Plant Collection. 31 records from KUBI Ichthyology Tissue Collection. 4 records from Rutgers University, Chrysler Herbarium - Macroalgae Collection. 1 records from Las monocotiledóneas mexicanas, una sinopsis florística. 5 records from Texas A&M University Insect Collection. 15 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 315 records from Naturalis Biodiversity Center (NL) - Crustacea. 1 records from The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae). 1 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 3 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Auckland Museum Botany Collection. 3 records from Global caridean shrimp fauna. 18000 records from KUBI Herpetology Collection. 1 records from PRECIS. 1 records from Actualización de la Colección Nacional de Peces dulceacuícolas mexicanos, ENCB. 27 records from Invertebrate Zoology Division, Yale Peabody Museum. 13 records from SMNS Herpetologie. 4 records from MBM - Herbário do Museu Botânico Municipal. 1 records from University of Tennessee Bryophyte Herbarium. 9 records from Bees of the genus Lasioglossum (Hymenoptera: Halictidae) from Greater Puerto Rico, West Indies. 2 records from Bird Collection of Museum and Institute of Zoology PAS. 1 records from Colección de Entomología - Diptera - Ceratopogonidae. 1 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 26 records from University of California Museum of Paleontology. 4 records from Naturalis Biodiversity Center (NL) - Porifera. 3 records from Natural History Museum, University of Tartu. 3 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 1 records from Actualización de la Colección de Artrópodos con importancia médica (CAIM), Laboratorio de Entomología, InDRE. 1 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 1 records from Fiocruz/CCER - Coleção de Ceratopogonidae. 400 records from UCM Amphibian and Reptile Collection (Arctos). 36 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 3 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 980 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 336 records from Naturalis Biodiversity Center (NL) - Mollusca. 1 records from SDSM Invertebrate Collections. 21 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 81 records from LSUMZ Bird Tissues. 2 records from UWBM Ornithology Collection. 1 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 50 records from CAS Ichthyology (ICH). 1 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 233 records from The System-wide Information Network for Genetic Resources (SINGER). 1 records from Revision of the Recent species of Exechonella Canu & Bassler in Duvergier, 1924 and Actisecos Canu & Bassler, 1927 (Bryozoa, Cheilostomata): systematics, biogeography and evolutionary trends in skeletal morphology. 95 records from Herps Specimens. 14 records from Mollusca specimens of Okinawa Prefectural Museum & Art Museum. 13 records from The Fish Collection at the Zoologische Staatssammlung München. 369 records from MPM Herpetology. 458 records from LSUMZ Birds Collection. 18 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 8 records from Collection Vermes - ZMB. 98 records from Mosses (S). 57 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Western Australian Museum provider for OZCAM. 123 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 4 records from CNMA/Colección Nacional de mamíferos. 1 records from Collection Aves (bird skeletons) SMF. 47 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 1 records from Insect Occurrence Data from MIZA. 2 records from Benthic Foraminifera from the Capricorn Group, Great Barrier Reef, Australia. 28 records from Reptile Specimens. 680 records from A global database for the distributions of crop wild relatives. 1 records from DBL_Life. 9 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from H.A. Stephens Herbarium. 2 records from KUBI Ornithology Collection. 1 records from KUBI Ichthyology Collection. 3 records from Revision of the Greater Antilles genus Paratrikona Spaeth, 1923 (Coleoptera: Chrysomelidae: Cassidinae: Dorynotini). 5 records from URM - Herbário Pe. Camille Torrand. 1 records from Herbarium of Taiwan Forestry Research Institute. 3 records from Brown University. 15 records from Fish Collection NRM. 4 records from Mollusca specimens of Manazuru Shell Museum. 657 records from UF FLMNH Ichthyology. 1 records from HUCS - Herbário da Universidade de Caxias do Sul. 9 records from TNHC Herpetology Collection. 2 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 2 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 136 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 205 records from Field Museum of Natural History (Zoology) Fish Collection. 87 records from Macaulay Library Audio and Video Collection. 1 records from Museu Paraense Emílio Goeldi - Lacertilia Collection. 1 records from DMNS Egg Collection (Arctos). 19 records from CAS Botany (BOT). 3 records from Herbario Nacional Colombiano (COL). 4 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 5 records from UB - Herbário da Universidade de Brasília. 5 records from Tallinn Botanic Garden. 904 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 2 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 2 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 4 records from CABI Bioscience Genetic Resource Collection. 3 records from MVZ Mammal Collection (Arctos). 1 records from NCSM Herpetology Collection. 84 records from The Brown University Foraminiferal Data Base (BFD). 1 records from Herbario de la Universidad de Sevilla. 208 records from Herpetology. 9 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 3289 records from Tropicos Specimen Data. 1 records from Queensland Museum provider for OZCAM. 1 records from Collection Crustacea - SNSD. 20 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 322 records from TTU Mammals Collection. 8 records from UMNH Reptiles and Amphibians Collection (Arctos). 4 records from A cybercatalogue of American sand fly types (Diptera, Psychodidae, Phlebotominae) deposited at the Natural History Museum, London. 1 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 4 records from Biological observations from the Dana Expedition Reports. 3 records from Revision and phylogenetic analysis of the orb-weaving spider genus Glenognatha Simon, 1887 (Araneae, Tetragnathidae). 1 records from A revision of the Neotropical spider genus Nops MacLeay (Araneae: Caponiidae) with the first phylogenetic hypothesis for the Nopinae genera. 4 records from The types of Phasmida in the Natural History Museum, London, UK. 3 records from CUMV Amphibian and Reptile Collection. 161 records from MPM Milwaukee Public Museum Invertebrate Zoology Collection. 129 records from BMSM Bailey-Matthews National Shell Museum. 5 records from Invertebrates Collection of the Swedish Museum of Natural History. 7 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 10 records from SIO Marine Vertebrate Collection. 663 records from MAL. 8 records from Lund Museum of Zoology - Insect collections (MZLU). 1 records from AUM Fish Collection. 50 records from Australian Museum provider for OZCAM. 319 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V12-122. 7 records from Type herbarium, Göttingen (GOET). 3 records from A new Calliprora species mining lead trees in Florida (Lepidoptera: Gelechiidae). 11 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 10 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 33 records from Estonian Museum of Natural History. 3 records from Collection Crustacea - ZMB. 2 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 2 records from Arachnida Araneae do Museu Nacional (MNRJ ARAC ARAN). 3 records from Mollusca specimens of Toyama Science Museum. 1 records from MLZ Bird Collection (Arctos). 1 records from Morphological revision of the Subgroup 1 Fauchald, 1970 of Marphysa de Quatrefages, 1865 (Eunicidae: Polychaeta). 1 records from Biologiezentrum Linz. 109 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 1 records from Coleção de Aves do Museu Nacional / UFRJ. 6 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 2 records from New Zealand Fungal and Plant Disease Collection (PDD). 1 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 20 records from Naturalis Biodiversity Center (NL) - Mammalia. 3 records from The AAU Herbarium Database. 3 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 4 records from UTEP Plants (Arctos). 8 records from Herpetile collection, Natural History Museum, University of Oslo. 1 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 2 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 47 records from CM Birds Collection. 21 records from DMNS Marine Invertebrate Collection (Arctos). 3 records from Herbarium (UNA). 5 records from Mollusca collection of National Museum of Nature and Science. 2 records from CHAS Malacology Collection (Arctos). 1 records from NCSM Ornithology Collection. 12 records from Field Museum of Natural History (Botany) Bryophyte Collection. 100 records from Fungi (S). 1 records from University of Ghana - Ghana Herbarium. 6 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 2 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 77 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 2 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 4 records from UWIZM Chrysomelidae Beetles. 196 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 1 records from Royal Ontario Museum Green Plant Herbarium (TRT). 1 records from Canadian Museum of Nature Insect Collection. 2 records from Invertebrates excl. Entomology at the Natural History Museum of Denmark. 161 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 38493 records from NMNH Extant Specimen Records. 1 records from Catálogo de los equinodermos recientes de México (Fase II). 577 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 59 records from Duke University. 17 records from Museums Victoria provider for OZCAM. 60 records from Ichthyology Collection - Royal Ontario Museum. 7 records from The Albert J. Cook Arthropod Research Collection. 37 records from SysTax - Zoological Collections. 11 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 77 records from AlgaTerra. 352 records from Illinois Natural History Survey Insect Collection. 538 records from CM Herps Collection. 1 records from Australian Antarctic Division Herbarium. 5 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 4 records from Collection Oligochaeta - ZIM Hamburg. 1 records from Invertebrate Paleontology Division, Yale Peabody Museum. 13 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 3 records from Marine invertebrate collection NTNU University Museum. 4 records from Los musgos de México. 1 records from Scolopendromorpha of New Guinea and adjacent islands (Myriapoda, Chilopoda). 2 records from R. L. McGregor Herbarium Lichen Collection. 5 records from Collection Malakologie - SNSD. 3 records from Invertebrate collection. 4 records from LSUMZ Herp Tissues. 21 records from Recent Invertebrates Specimens. 1 records from MSUM Ichthyology and Herpetology Collections. 2 records from The Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Fiocruz/CTIOC - Coleção de Triatomíneos do Instituto Oswaldo Cruz. 4 records from Collection Pisces SMF. 39 records from CABI Bioscience Fungus Collection. 1 records from MEXU/Tipos de plantas vasculares. 3 records from Lund Museum of Zoology (MZLU). 5 records from Natural History Museum, Vienna - Herbarium W. 3 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 97 records from Bryophyte herbarium, Göttingen (GOET). 2 records from Revision of Alaptus (Hymenoptera: Mymaridae) in the Holarctic region, with taxonomic notes on some extralimital species. 1 records from Bee Biology and Systematics Laboratory. 19 records from University of Puerto Rico Mayagüez Invertebrate Collection. 3 records from CUMV Fish Collection. 1 records from UAZ Mammals. 2 records from EURISCO, The European Genetic Resources Search Catalogue. 11715 records from The New York Botanical Garden Herbarium (NY). 15 records from Field Museum of Natural History (Botany) Lichen Collection. 1 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 2 records from Naturalis Biodiversity Center (NL) - Paleobotany. 5 records from Myriapoda - SMF. 65 records from Mosquito Occurrence Dataset. 2 records from Canadian Museum of Nature Mammal Collection. 24 records from Collection Arachnology SMF. 7 records from University of Tennessee Fungal Herbarium. 23 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Herpetology Collection - Royal Ontario Museum. 153 records from University of Michigan Museum of Zoology, Division of Mollusks. 5 records from Name-bearing types of butterflies (Lepidoptera, Papilionoidea), in the National Museums of Scotland, Edinburgh. 20 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 1 records from NCSM Mammals Collection. 271 records from Geneva Herbarium – General Collection (G). 2 records from Two new species of flattie spiders (Araneae: Selenopidae) and descriptions of undescribed males from the Caribbean. 3 records from Brigham Young University Arthropod Museum. 65 records from Royal Botanic Garden Edinburgh Herbarium (E). 87 records from LSUMZ Herps Collection. 40 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 2 records from herbario. 55 records from Arizona State University Vascular Plant Herbarium. 1 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 1 records from SDNHM Herpetology Collection. 14 records from Global compendium of Aedes albopictus occurrence. 188 records from RBINS DaRWIN. 33 records from University of Florida Invertebrate Paleontology. 19 records from Lund Botanical Museum (LD). 937 records from Natural History Museum (London) Collection Specimens. 5 records from University of Tennessee Lichen Herbarium. 1 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 1 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 1 records from Computarización del Herbario ENCB. Fase II. Base de datos de los ejemplares de la familia Burseraceae y Nyctaginaceae y base de datos digitalizada de los ejemplares tipo de plantas vasculares del Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 10 records from Sukkulentensammlung Zürich. 9 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 5 records from Aves MZS. 1 records from Botanic Garden of the Finnish Museum of Natural History. 110 records from Collection Herpetology SMF. 1187 records from AMNH Herpetology Collections. 1 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 9 records from The nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2964 records from Phanerogamic Botanical Collections (S). 3 records from MMNH Museum Bird Collection. 2 records from Lichen Herbarium Berlin. 5009 records from UF Invertebrate Zoology. 636 records from Paleobiology Database. 4 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 5 records from Vertebrate Paleontology Division, Yale Peabody Museum. 35 records from Bioversity Collecting Mission Database. 18 records from The Vascular Plant Collection at the Herbarium Tubingense. 1 records from A new species of extinct Late Quaternary giant tortoise from Hispaniola. 42 records from Planktic foraminifera counts in surface sediment samples. 1 records from Taxonomic revision and phylogeny of the ant genus Prenolepis (Hymenoptera: Formicidae). 3 records from Jardin botanique de Montréal (JBM). 1 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 129 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 2 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 131 records from KUBI Mammalogy Collection. 78 records from University of Michigan Museum of Zoology, Division of Fishes. 6 records from ZFMK Orthopteroidea collection. 3 records from Global compendium of Aedes aegypti occurrence. 395 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 6 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1955 records from Abundance of planktonic foraminifera in sediment core V12-122. 6 records from Fish collection, Natural History Museum, University of Oslo. 1 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 365 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Senckenberg - CeDAMar Resource. 11 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 78 records from UTA Herpetology. 100 records from Snow Entomological Museum Collection. 1 records from Mammals housed at MHNG, Geneva. 439 records from Field Museum of Natural History (Zoology) Bird Collection. 114 records from Guadeloupe_Herbier. 2 records from Arizona State University Charles W. O'Brien Collection. 4 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 65 records from United States National Plant Germplasm System Collection. 28 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 10 records from NPL collections. 10 records from Herbaria of the University and ETH Zürich. 1 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 6081 records from University of Florida Herpetology. 10 records from DORSA - German Orthoptera Collections. 1325 records from Michigan State University Herbarium Lichens. 1 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 4 records from Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae).. 7 records from Taxonomic revision of the flavopalliata species group of Signiphora (Hymenoptera: Signiphoridae). 76 records from MEL AVH data. 2 records from Canadian Museum of Nature Amphibian and Reptile Collection. 242 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Zoology (Museum of Evolution - Uppsala). 378 records from Entomology Division, Yale Peabody Museum. 1 records from KU Museum of Invertebrate Paleontology. 34 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Platyhelminthes. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences